ANALISIS PENGARUH KEPUASAN KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PRIMA INDOJAYA MANDIRI KABUPATEN LAHAT - Andayani, Melia (MOTIVASI, 2020)
ABSTRACTPurpose - This study aims to determine the analysis of the influence of job satisfaction, work motivation and work discipline on employee performance of PT. Prima Indojaya Mandiri.Design/methodology - This research is a causal research that is to see the effect of the dependent variable with independent variable. Data collection techniques using questionnaires and documentation. The total population 42 employees. The analysis technique used multiple regression analysis which is to analyze the effect of variable and hypothesis test used partial test (t test) and simultaneous test (F test).Findings - The results showed that probability for job satisfaction was P value = 0,895> 0,050, work discipline  P value = 0,004 > 0,050, and work motivation was P value = 0,002 > 0,050 that means job satisfaction didn’t have a significant effect on employee performance while the work discipline  and work motivation have a significant effect on employee on PT. Prima Indojaya Mandiri. Based on the F test, the variable of job satisfaction, work discipline and work motivation have a simultaneous influence on employee performance with a significant level 0, 00 (P value < 0,05).Keywords : Motivation, Work Discipline, and Employee Performance.